Expression of Chlamydia pneumoniae Polymorphic Membrane Protein Family Genes - Grimwood, Jane (American Society for Microbiology, 2001)
The genome of the obligate intracellular bacterium Chlamydia pneumoniae CWL029 encodes a family of 21 proteins with predicted outer membrane localization. These polymorphic membrane proteins (Pmps) are heterogeneous in both amino acid sequence and predicted size but are unified by the conserved amino acid motifs GGAI and FXXN repeated in the N-terminal half of each protein. Reverse transcriptase PCR analysis showed that all pmp genes are transcribed. To determine whether all proteins are expressed, specific antisera were generated by immunization with mutually exclusive synthetic peptides representing each of the 21 predicted Pmps. Each antiserum reacted with, and was typically immunospecific for, the corresponding peptide immunogen by enzyme-linked immunosorbent assay. Western blot analyses of purified elementary bodies showed that 11 of the 21 Pmps were detectable. Attempts to demonstrate by Sarykosyl fractionation that the Pmps were localized to the outer membrane revealed that several of the Pmps were unstable and readily degraded. Analyses of additional C. pneumoniae strains showed that although some Pmps are conserved, others vary between strains, in both molecular weight and level of expression.